Risk Factors of Type 2 Diabetes and Cardiovascular Diseases among Saudi Arabian Adolescents - Albow, Baker M.; Alenezy, Awwad K. (Pakistan Journal of Nutrition, 2016)
This study aimed to investigate the prevalence of risk factors for Type2 Diabetes and Cardiovascular Diseases among Saudi Arabian adolescents of Arar region. A descriptive epidemiological cross sectional study was conducted with 200 participants (aged 14-19 years) randomly selected from secondary and high schools in the northern border region, KSA. Fasting blood glucose (FBG), total cholesterol (TC) and triacylglycerols (TG) serum levels along with glycated hemoglobin (HbAlc) for early screening of risk factors for T2DM and CVDs in the school setting. FBG, HbAlc and TG mean levels were significantly higher in female subgroup when compared to those of male subgroup. Our results revealed that 68 (34%) of our participants were over weighed, 56 (28%) were class I obese, 40 (20%) were class II obese and 14 (7%) were class III obese. There was a significant positive correlation between BMI and HbAlc (r = 0.33, p